Prokineticin 1 is up‐regulated by insulin in decidualizing human endometrial stromal cells. Issue 1 (7th August 2017) - Ujvari, Dorina; Jakson, Ivika; Oldmark, Cecilia; Attarha, Sanaz; Alkasalias, Twana; Salamon, Daniel; Gidlöf, Sebastian; Hirschberg, Angelica Lindén
Abstract: Prokineticin 1 (PROK1), a hypoxia‐regulated angiogenic factor, has emerged as a crucial regulator of embryo implantation and placentation. Dysregulation of PROK1 has been linked to recurrent pregnancy loss, pre‐eclampsia, foetal growth restriction and preterm birth. These pregnancy complications are common in women with obesity and polycystic ovary syndrome, i.e. conditions associated with insulin resistance and compensatory hyperinsulinaemia. We investigated the effect of insulin on PROK1 expression during in vitro decidualization. Endometrial stromal cells were isolated from six healthy, regularly menstruating women and decidualized in vitro . Insulin induced a significant dose‐dependent up‐regulation of PROK1 on both mRNA and protein level in decidualizing endometrial stromal cells. This up‐regulation was mediated by hypoxia‐inducible factor 1‐alpha (HIF1α) via the phosphatidylinositol 3‐kinase (PI3K) pathway. Furthermore, we demonstrated that PROK1 did not affect the viability, but significantly inhibited the migration of endometrial stromal cells and the migratory and invasive capacity of trophoblast cell lines. This in vitro study provides new insights into the regulation of PROK1 by insulin in human decidualizing endometrial stromal cells, the action of PROK1 on migration of endometrial stromal cells, as well as migration and invasion of trophoblasts. We speculate that hyperinsulinaemia may be involved in the mechanisms by which PROK1 is linked to placenta‐related pregnancy complications.